1102 ARRYTHMOGENIC CARDIOMYOPATHY: LESSONS FROM A LARGE FAMILY. (15th December 2022) - Mancinelli, Antonella; Scatigno, Agnese; Iacovoni, Attilio; Abete, Raffaele; Senni, Michele; Iascone, Maria; Iorio, Annamaria
Abstract: Background: Arrhythmogenic cardiomyopathy is a genetically-inherited cardiomyopathy. PKP2 mutations are the most common cause of the disease, associated with conventional ARVC phenotype. Case presentation: We presented a 14 years old sportswoman admitted to our emergency department for cardiac arrest-related to ventricular fibrillation. The patient was asymptomatic leading up to cardiac arrest. At admission, she met the diagnosis of AC with bi-ventricular involvement (T negative waves in V1-V6 and inferior leads; severe biventricular dysfunction with fibrofatty replacement involving both ventricles). Family history revealed that her cousin, a 15 years competitive athlete, received a recent diagnosis of ARVC, wherein pathogenetic variant p.Tyr857_Lys859 in heterozygosity in the PKP2 gene was found. As expected, the index case presented the same mutations in PKP2 gene, and no other mutations were found. Implanted cardioverter defibrillator (ICD) and strength follow-up, including heart failure management, was performed. Cascade screening of family members allowed us to identify 19 mutations carriers. Of these, 5 patients were identified to have disease expression. The first to be studied was her 9 years old sister, who involved in high level of sport activities. She presented abnormal ECG with negative T waves in V2-V4, significance burden of premature ventricular complex (PVC >500/24 h) with mild right ventricle dilatation. Of others family members, four patients presented early signs of myocardial disease and significant arrhythmias burden. Except for one patient, all these members were involved in amateur sport activities. Two members had signs of left ventricle (LV) involvement (inverted T waves in leads V4–V6 and inferior leads, LV wall motion abnormalities and late enhancement), whereas one patient (P3) showed a fulfilled ARVD. Three patients presented significant PVC on 24-hour ambulatory ECG monitoring (PVC >500/24 h) (P2, P3 and P5). The arrhythmic burden was more pronounced in two young patients having a sports activity (P2 and P3). This trend was also confirmed at exercise testing. Except for one patient, these findings appear to be related to sport activity, even if this is no high-intensity activity. Among other carriers of pathogenic mutation, three patients showed ECG abnormalities in infero-lateral leads and significance PVC at 24-hour ECG monitoring in absence of other findings related-cardiomyopathy. All family members carried PKP2 mutation were restricted in sports activities, and, in patients presented early disease and arrhythmogenic burden, treatment with beta-blockers was started. Conclusion: In this family presenting PKP2 mutation, heterogenicity of disease expression and a close relationship with sport activity was found. This large family case encourages future ACM studies to better understand disease expression and their relationship with sports activity across the entire ACM phenotypic spectrum and ages. Also, this case underscores the importance of early familiar screening, including children involved high-level of sports activity.